#TITLE_ALTERNATIVE# - ELDHIE SYAÃ‚Â’BANNI (NIM. 101 06 087); Pembimbing Dumaria R. Tampubolon, Ph.D; Ocke Kurnian, RAHMAT
In health insurance, the coverage may be classified into in-patient treatment and out-patient treatment. Surgery may be classified into either one depending on the type of surgeries conducted. In this skripsi (final project), the claims data analyzed are claims from surgical procedures for in-patient treatment. Variables for the claims data are: claim frequency, number of days hospitalized (hospital day), and claim amount. Each variable is modeled by a parametric model. A compound model is used to analyze the aggregate loss (claims) and the aggregate hospital day for several age groups. The probability of the aggregate loss at discrete points is determined using recursive method. The risk premium is determined theoretically and by Monte-Carlo simulation and it is found that the risk premium obtained are similar.